(3GdJdhjMGJ aj GdefWb hGdMceIs - (3jMji Hf qMnHT Hf CejQc, CHh GdaJhM, TgGH GdOjf, GdSgQhQOj,J (B587 (3g` s
(3ChdgG (B:s
(3GdSHMGJ dLdGdc Gddge jG bjhe GaV YdjfG gPg JdhjMGJ Edi CUhd ef GdMceI BJjI Ydi GdYdhe GdKdGKjI s
(3BNQgG (B:s
(3aEf GdEfaYGd GdZjQ GdeJfGgi hGdaYd GdZjQ eJfGgi Ydi SHjd GdhSGWI Ke Ef GdCadGc s
(3QJH Ydi KdGKI Ydhe GdefWb hGdWHjYi hGdGdgis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B140 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B189s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3Gdadcs